Optical contrast of oil dispersed in seawater under windy conditions - Otremba Z.; Zielinski O.; Hu C. (Journal of the European Optical Society-Rapid Publications, 2013)
Oil pollution of natural waters represents a serious threat for aquatic ecosystems, and the assessment of the degree of pollution requires measurement strategies including remote sensing and modeling. While surface oil pollution is relatively easy to detect with radar or optical remote sensing, underwater oil emulsions can only be detected using visible light as an information carrier. Here the Michelson contrast of sea area polluted by an oil-in-water emulsion under various wind conditions is simulated through Monte-Carlo modeling. The results show the premise for optimal direction of observations in which the possibility of detecting the emulsified oil is maximized.